Studi Komparatif Pemikiran M. Quraish Shihab dan Amina Wadud Tentang Nusyûz - Imarotuz Zulfa (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2022)
Marriage is a physical and spiritual bond between a woman and a man with the intention of forming a family with tranquility, love, and mercy. In marriage, there are rights and obligations between husband and wife that must be fulfilled. If a husband and wife do not perform their obligations, it can be said to be nusyūz. This article reviews the wife nusyūz and husband nusyūz solutions based on Q.S. an-Nisa verses 34 and 128 in a comparison of M. Quraish Shihab and Amina Wadud's thoughts. The research approach uses library research with the main source of Tafsir Al-Misbah by M. Quraish Shihab and the Qur'an and Women Book by Amina Wadud. This study uses the comparative-descriptive method by data collection techniques using documentation. The results of the research concluded that M. Quraish Shihab and Amina Wadud have differences in formulating solutions to the nusyūz conflict. The word ḍaraba which is found in Q.S an-Nisa verse 34, is more defined as